A microfluidic study of bubble formation and coalescence tuned by dynamic adsorption of SDS and proteins. (July 2023) - Deng, Boxin; Schroën, Karin; de Ruiter, Jolet
Abstract: During foaming, bubbles are formed at ( sub)millisecond time scales, and emulsifier adsorption determines bubble formation and stabilisation against coalescence. Here we introduce a microfluidic device, in which bubbles are formed in two distinct pressure regimes at low versus high pressures, and emulsifier adsorption can be inferred from the easily-monitored dynamics of bubble formation and coalescence, as well as the bubble properties. We studied dynamic adsorption for various types and concentrations of emulsifiers, namely sodium dodecyl sulfate (SDS; 0.05–3% wt.) and various proteins (5% wt.) including whey protein isolate (WPI), β-lactoglobulin (β-lac), and bovine serum albumin (BSA). The results show that as SDS concentration increases up to 3% wt., the bubble formation time decreases in the low-pressure regime due to the enhanced adsorption of SDS, yet increases in the high-pressure regime due to the promoted 'dripping-jetting' transition; in both pressure regimes the neck thinning process slows down, leading to longer bubble growth time and thus larger bubble size. To suppress coalescence of bubbles formed at time scales down to 10 μs, SDS is the most efficient, followed by BSA, WPI, and finally, β-lac; this is ascribed to the dynamics of emulsifier adsorption, e.g., the resulting dynamic surface tension. To conclude, our microfluidic study highlights the dynamic effects in the presence of SDS and proteins during bubble formation, even at high concentrations. This means that to explain the properties of a freshly-formed foam product, it is crucial to understand (and thereafter manipulate) emulsifier adsorption at time scales relevant to bubble formation and coalescence. Graphical abstract: Image 1 Highlights: Bubble formation and coalescence are studied simultaneously in one microfluidic device. Dynamic surface tension dictates bubble coalescence stability at (sub)milliseconds. Fast adsorption for SDS and interfacial network formation for protein lead to large bubbles. High emulsifier concentration leads to satellite bubble formation. Flow patterns are monitored in the bubble formation unit.